(untitled) - Sheimo, Michael D. (Chicago, 1994)
Stock Market Rules, Third Edition, is that book, an in-depth, up-to-date examination of the 50 axioms that will most help investors gain the edge in today's technologically supercharged markets. Investors needing authoritative, hands-on guidance will look to this updated edition for its: Short sections covering the 50 most immediately useful rules, asy-to-read yet analytical approach, Arrangement by research, strategy, and other major topic areas.
Keywords: Bank marketing,Stock exchanges